2020
DOI: 10.1111/opn.12320
|View full text |Cite
|
Sign up to set email alerts
|

Dog‐assisted interventions and outcomes for older adults in residential long‐term care facilities: A systematic review and meta‐analysis

Abstract: Objective To comprehensively review studies on dog‐assisted interventions (DAIs) among older people in residential long‐term care facilities (RLTCFs) and to provide an overview of their interventions, outcomes and methodological quality. Method We searched 18 electronic databases to identify English articles (published January 2000–December 2019) reporting on well‐defined DAIs targeting older adults (≥65 years) in RLTCF. Data were extracted by two independent reviewers. Descriptive statistics were produced for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…This study comes from a relativist paradigm using interpretation of combined data from direct observation and participant feedback to address a gap in the literature (Jain et al, 2020). It revealed a number of immediate and short-term impacts of the DAI on care home resident's overall wellbeing.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study comes from a relativist paradigm using interpretation of combined data from direct observation and participant feedback to address a gap in the literature (Jain et al, 2020). It revealed a number of immediate and short-term impacts of the DAI on care home resident's overall wellbeing.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…Innovations that foster person Dog-assisted intervention (DAI) is one of the most common forms of AAI and is the focus of this study. A recent systematic review and meta-analysis identified over 40 research studies examining the impact of DAI on older people living in care homes (Jain et al, 2020). This review showed that existing research focuses almost exclusively on quantitatively evaluated impacts, often using a single outcome to measure changes over time or between groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of how visits from dogs affect nursing home residents have mainly focussed on long-term benefits measured by psychometric scales evaluating symptoms of depression, loneliness, quality of life, impairment level and agitated behaviour in nursing home residents or persons with dementia. Recently, review papers have outnumbered papers reporting experimental studies, and authors generally agree that the evidence base for specific effects of dog visits in nursing homes is weak and inconclusive [ 5 10 ]. Several reviews point out that the use of very different study settings makes it difficult to reach definite conclusions about specific effects of dog visits [ 6 8 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%